2022
DOI: 10.3389/fimmu.2021.766970
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Erythrocytes From Goose (Anser domesticus) Can Be Associated With Phagocytosis and Respiratory Burst Generation

Abstract: In the lumen of blood vessels, there are large numbers of erythrocytes, which are approximately 95% of the total blood cells. Although the function of erythrocytes is to transport oxygen in the organism, recent studies have shown that mammalian and teleost erythrocytes are involved in the immune response against bacterial infections. However, the immune mechanisms used by avian erythrocytes are not yet clear. Here, we demonstrated that erythrocytes from goose have the ability to phagocytose as well as conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Although ion channels are important molecular targets for the intercellular transport of Pb, it is highly likely that other transport pathways exist, considering that most of the Pb in the blood is in the form of binding to protein. Endocytosis, an important pathway for intercellular transport of macromolecules, is a process by which cells absorb external material by engulfing it with the cell membrane, which is closely related to a variety of life activities, such as immune response, neurotransmitter transport, cell signal transduction, and cellular and tissue metabolic balance. , In general, endocytosis can be divided into pinocytosis and phagocytosis. , Although conventional wisdom holds that endocytosis occurs mainly in specialized cells of the immune system and red blood cells lack endocytosis due to the absence of mitochondria, studies have found that particles and microorganisms may be transferred into red blood cells in a manner similar to endocytosis. In this study, we found for the first time that Pb-binding proteins in blood cells are primarily involved in phagocytosis, which is related to the level of Pb in the blood (Figure C). This identifies two possible different understandings for intercellular transport of Pb, one is the phagocytosis-like (precisely, internalization) transport pathway, which transports Pb-binding proteins or small molecules into red blood cells through internalization, and the other is phagocytes such as macrophages, which engulf senescent or damaged red blood cells that are attached to Pb and transport Pb into the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Although ion channels are important molecular targets for the intercellular transport of Pb, it is highly likely that other transport pathways exist, considering that most of the Pb in the blood is in the form of binding to protein. Endocytosis, an important pathway for intercellular transport of macromolecules, is a process by which cells absorb external material by engulfing it with the cell membrane, which is closely related to a variety of life activities, such as immune response, neurotransmitter transport, cell signal transduction, and cellular and tissue metabolic balance. , In general, endocytosis can be divided into pinocytosis and phagocytosis. , Although conventional wisdom holds that endocytosis occurs mainly in specialized cells of the immune system and red blood cells lack endocytosis due to the absence of mitochondria, studies have found that particles and microorganisms may be transferred into red blood cells in a manner similar to endocytosis. In this study, we found for the first time that Pb-binding proteins in blood cells are primarily involved in phagocytosis, which is related to the level of Pb in the blood (Figure C). This identifies two possible different understandings for intercellular transport of Pb, one is the phagocytosis-like (precisely, internalization) transport pathway, which transports Pb-binding proteins or small molecules into red blood cells through internalization, and the other is phagocytes such as macrophages, which engulf senescent or damaged red blood cells that are attached to Pb and transport Pb into the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [35] has indicated that 30-40% of elective surgical patients experience preoperative anemia, which could complicate surgery, increase the likelihood of transfusion or admission to the intensive care unit, elevate the risk of infection events, and prolong hospital stays. Red blood cells, like white blood cells, play a crucial role in the body's defense mechanism, as they clear immune complexes by binding to C3b receptors [36]. In anemic patients, the immune adherence activity of red blood cells to C3b is significantly reduced, leading to a decline in immune function and weakening of the phagocytic action against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes, the most abundant blood cell type, occupy a quarter of the total cell numbers within the human body. 24 Erythrocytes harbor various distinctive properties such as unmatched long circulation, biocompatibility and biodegradability that make them appealing vascular carriers for in vivo delivery of natural and synthetic payloads. 9 , 25 Although our previous study has suggested a BBR erythrocytes-Hb self-assembly delivery system, 12 the metabolic aspect, targeted delivery and dose–effect relationship of BBR mediated by erythrocytes have not yet been clearly clarified.…”
Section: Discussionmentioning
confidence: 99%